1990
DOI: 10.1002/jnr.490260113
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ganglioside abnormalities in pcd mutant mice

Abstract: The distribution of cerebellar gangliosides was studied in Purkinje cell degeneration (pcd/pcd) mutant mice at postnatal days 25, 30, 50, and 150. These mutants lose the majority of Purkinje cells between 18 and 50 days of age. A reactive gliosis accompanies Purkinje cell loss and a partial loss of granule cells occurs in pcd/pcd mice older than p50. Purkinje cell loss is associated with significant reductions in cerebellar weight and ganglioside concentration. This neuronal loss was also developmentally corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Although gangliosides GT1a and LD1 comigrate on the HPTLC in this solvent system, previous studies showed that LD1 [disialosylparagloboside (disialosyl‐nLc4Cer)] is the major ganglioside in this band (Chou et al. 1990; Seyfried and Yu 1990). In addition, asialo‐GM2 (GA2) and asialo‐GM1 (GA1) were elevated in the Hexb −/− and the β‐gal −/− mice, respectively (Fig.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Although gangliosides GT1a and LD1 comigrate on the HPTLC in this solvent system, previous studies showed that LD1 [disialosylparagloboside (disialosyl‐nLc4Cer)] is the major ganglioside in this band (Chou et al. 1990; Seyfried and Yu 1990). In addition, asialo‐GM2 (GA2) and asialo‐GM1 (GA1) were elevated in the Hexb −/− and the β‐gal −/− mice, respectively (Fig.…”
Section: Methodsmentioning
confidence: 75%
“…1987; Chou et al. 1990Seyfried and Yu 1990). Interestingly, these mice also express retinal degeneration and visual impairment (Mullen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gangliosides GD1a and GT1b are enriched in neuronal and synaptic membranes, whereas ganglioside GD3 is enriched in reactive glial cells and is a good marker for neurodegeneration (18-21). In the mouse cerebellum, GD1a is enriched in granule cells while LD1/GT1a is enriched in Purkinje cells (22, 23). Changes in these gangliosides are indicative of changes in granule cells and Purkinje cells, respectively (19, 20, 22, 24).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that an increased shedding of membrane fragments from myelin leads to an increased cerebrospinal fluid (CSF) sul fatide concentration. In vascular dementia, an increased concentration of sulfatide in CSF has been found, proba bly reflecting demyelination [19,20], Ganglioside GD3 is a minor ganglioside in the normal brain, but increases in reactive astrocytes after different forms of trauma [21] and neuronal degeneration [22], Therefore, ganglioside GD3 has a potential as a biochemi cal marker for reactive gliosis.…”
Section: Introductionmentioning
confidence: 99%